Impact of regional pest control on pesticide application in China from a perceived risks perspective - Xu, Bin; Kong, Fanzhu (Frontiers in Sustainable Food Systems, 2024)
The Regional Pest Control program represents a strategic intervention aimed at optimizing pesticide use in crop production, thereby mitigating the environmental impact of agricultural non-point source pollution from pesticides and fostering the development of high-quality agriculture. This study examines the influence of farmers’ perceived risks on the adoption of the Regional Pest Control program and evaluates its effect on pesticide application across a nationally representative dataset from Heilongjiang, Jiangsu, Anhui, Hubei, and Sichuan provinces. To account for unobserved heterogeneity, an endogenous switching regression model was employed. The findings reveal that farmers’ perceived risks associated with the Regional Pest Control program significantly deter its adoption. Furthermore, the program has been effective not only in reducing the frequency of pesticide applications but also in increasing the usage of pesticides with lower acute toxicity levels. Notably, the impact of the Regional Pest Control program on pesticide application demonstrates considerable variation in accordance with farmers’ risk attitudes.